Experimental performance of buckling-restrained braces with steel cores of H-section and half-wavelength evaluation of higher-order local buckling. Issue 4 (April 2017) - Li, Wei; Wu, Bin; Ding, Yong; Zhao, Junxian
To prevent lower-order local buckling of H-section steel core, an improved type of buckling-restrained braces named buckling-restrained brace with H-section steel core was proposed by the authors. This article further investigates the effect of configuration details on seismic performance of buckling-restrained braces with H-section steel core and compares two half-wavelength calculation methods for higher-order local buckling of H-section steel core. First, quasi-static cyclic tests are described on two newly designed buckling-restrained braces with H-section steel cores and another buckling-restrained brace with flat steel core. Then, Bleich's and Lundquist's methods are reviewed for evaluating half wavelength of higher-order local buckling based on elastoplastic buckling theory of plates and compared with the test results of four buckling-restrained braces with H-section steel core including the two from a previous test. It is found from the test results that due to H-section steel core's higher self-stability, the compression force fluctuation was not observed on the hysteretic loops of buckling-restrained brace with H-section steel core with even larger clearance but on the buckling-restrained brace with flat core. The buckling-restrained brace with H-section steel core was also advantageous over the buckling-restrained brace with flat core in terms of having lower compression strength adjustment factor β . A stopper in the middle of the core member and the gradual change of cross section of the core plate around the end of stiffeners could help to improve the fatigue performance of buckling-restrained braces. The test results also confirmed that Lundquist's theory was more reliable for evaluating the half wavelength of higher-order local buckling for H-section steel core.